Alarm/will/sound: Sound design, modelling, perception and composition cross-currents. Issue 1 (30th May 2019) - Sigman, Alexander; Misdariis, Nicolas
Abstract : An ongoing international arts-research-industry collaborative project focusing on the design and implementation of innovative car alarm systems, alarm/will/sound has a firm theoretical basis in theories of sound perception and classification of Pierre Schaeffer and the acousmatic tradition. In turn, the timbre perception, modelling and design components of this project have had a significant influence on a range of fixed media, electroacoustic and media installation works realised in parallel to the experimental research. An examination of the multiple points of contact and cross-influence between auditory warning research and artistic practice forms the backbone of this article, with an eye towards continued development in both the research and the artistic domains of the project.